2020
DOI: 10.1016/j.bbr.2020.112603
|View full text |Cite
|
Sign up to set email alerts
|

Binocular rivalry dynamics associated with high levels of self-reported autistic traits suggest an imbalance of cortical excitation and inhibition

Abstract: An imbalance in cortical excitation and inhibition (E/I) may underlie both social and nonsocial symptoms of autism spectrum conditions (ASC). Recent work suggests that an E/I imbalance may underlie some of the sensory differences that are characteristic of ASCs such as anomalous perception. Binocular rivalry dynamics are thought to reflect the balance of E/I in the brain and could serve as a behavioural biomarker for ASC. Previous studies of clinical ASC populations have found a slower rate of binocular rivalr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…However, that study employed a large stimulus size, which is known to be biased toward mixed perception 20 . Later studies used smaller apertures and found longer durations of mixed perceptions (and fewer perceptual alternations) in adults with autism 31 33 and in neuro-typical adults with an elevated autistic symptomology 36 . Several studies have found that stereoacuity is reduced in autism compared to controls 37 , 38 and people with autism are more likely to have binocular vision disruptions due to strabismus and amblyopia 2 , 38 42 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, that study employed a large stimulus size, which is known to be biased toward mixed perception 20 . Later studies used smaller apertures and found longer durations of mixed perceptions (and fewer perceptual alternations) in adults with autism 31 33 and in neuro-typical adults with an elevated autistic symptomology 36 . Several studies have found that stereoacuity is reduced in autism compared to controls 37 , 38 and people with autism are more likely to have binocular vision disruptions due to strabismus and amblyopia 2 , 38 42 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated CBR in autism 30 36 , including mixed perception, but have not classified piecemeal or superimposition components. The first study concerning CBR and autism did not find a significant difference between autistic and control groups 30 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, BI has attracted more and more attention, especially in the field of dyslexia 11 and autism. 3 , 12 This is dependent on the imbalance of BR as one of the external manifestations of E/I balance condition, and which can be observed and studied by various tests. However, the studies focused on BI in vision problems were relatively limited, especially with myopia.…”
Section: Discussionmentioning
confidence: 99%
“…As to the mechanisms of GABAergic inhibitory dysfunction, the link with core ASD symptoms in humans is still under investigation. The deficit in binocular rivalry, a visual function that is thought to rely on the balance of excitation/inhibition in the visual cortex, has been observed in ASD individuals ( Dunn and Jones, 2020 ). The link between GABA and binocular rivalry dynamics was found specifically absent in ASD pointing to an insufficient GABA inhibitory function ( Dunn and Jones, 2020 ).…”
Section: Introductionmentioning
confidence: 99%